Dietary intake of acrylamide and endometrial cancer risk in the European Prospective Investigation into Cancer and Nutrition cohort. - Obón-Santacana, M; Kaaks, R; Slimani, N; Lujan-Barroso, L; Freisling, H; Ferrari, P; Dossus, L; Chabbert-Buffet, N; Baglietto, L; Fortner, RT; Boeing, H; Tjønneland, A; et al. (2014)
BACKGROUND: Three prospective studies have evaluated the association between dietary acrylamide intake and endometrial cancer (EC) risk with inconsistent results. The objective of this study was to evaluate the association between acrylamide intake and EC risk: for overall EC, for type-I EC, and in never smokers and never users of oral contraceptives (OCs). Smoking is a source of acrylamide, and OC use is a protective factor for EC risk. METHODS: Cox regression was used to estimate hazard ratios (HRs) for the association between acrylamide intake and EC risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Acrylamide intake was estimated from the EU acrylamide monitoring database, which was matched with EPIC questionnaire-based food consumption data. Acrylamide intake was energy adjusted using the residual method. RESULTS: No associations were observed between acrylamide intake and overall EC (n=1382) or type-I EC risk (n=627). We observed increasing relative risks for type-I EC with increasing acrylamide intake among women who both never smoked and were non-users of OCs (HRQ5vsQ1: 1.97, 95% CI: 1.08-3.62; likelihood ratio test (LRT) P-value: 0.01, n=203). CONCLUSIONS: Dietary intake of acrylamide was not associated with overall or type-I EC risk; however, positive associations with type I were observed in women who were both non-users of OCs and never smokers.